2008
DOI: 10.1002/ptr.2548
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant activities of nutmeg oil of Myristica fragrans

Abstract: The purpose of this study was to investigate the anticonvulsant activity of the volatile oil of nutmeg, the dried seed kernel of Myristica fragrans Houtt, using well-established animal seizure models and to evaluate its potential for acute toxicity and acute neurotoxicity. The volatile oil of nutmeg (nutmeg oil) was tested for its effects in maximal electroshock, subcutaneous pentylenetetrazole, strychnine and bicuculline seizure tests. All the experiments were performed at the time of peak effect of nutmeg oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…A number of recent reports listed between 27–37 components present at various concentrations as determined by GC/MS. In two independent studies by Wahab et al and Piaru et al, the total number of compounds identified in the essential oil was 37 (Piaru et al 2012, Wahab et al 2009). In other studies, Du et al reported 27 compounds, Muchtaridi and co-workers listed 32 compounds while Piras et al identified 30 compounds (Du et al 2014, Muchtaridi et al 2010, Piras et al 2012).…”
Section: Chemistry Of Major Secondary Metabolites Of Nutmegmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent reports listed between 27–37 components present at various concentrations as determined by GC/MS. In two independent studies by Wahab et al and Piaru et al, the total number of compounds identified in the essential oil was 37 (Piaru et al 2012, Wahab et al 2009). In other studies, Du et al reported 27 compounds, Muchtaridi and co-workers listed 32 compounds while Piras et al identified 30 compounds (Du et al 2014, Muchtaridi et al 2010, Piras et al 2012).…”
Section: Chemistry Of Major Secondary Metabolites Of Nutmegmentioning
confidence: 99%
“…Wahab et al reported a dose-dependent activity of nutmeg oil in various animal seizure models (Wahab et al 2009). The oil exerted significant anticonvulsant effect against seizures induced by maximal electroshock, pentylenetetrazole, and strychnine, at doses that did not impair locomotor activity.…”
Section: Pharmacological Investigation Of Nutmeg Extracts and Essentimentioning
confidence: 99%
“…Wahab and his team analysed the anticonvulsant potency of the volatile oil of nutmeg ( Myristica fragrans Houtt., Myristicaceae), using popular seizure models for animals such as the maximal electroshock model or the PTZ, strychnine and bicuculline test. The action of nutmeg oil started rapidly but the anticonvulsive effect did not last very long, however, it was significantly anticonvulsant effective in the MES model.…”
Section: Anticonvulsive Action and Treatment Of Epilepsymentioning
confidence: 99%
“…Results of this study concluded that O. basilicum EOs possess anticonvulsant and CNS depressant potentials mediated via central GABAergic receptors. Wahab et al (2009) reported the anticonvulsant efficiency of EO from Myristica fragrans Houtt. (nutmeg) using various animal models of seizures.…”
Section: Other Neuropharmacological Actions Of Essential Oilsmentioning
confidence: 99%